Improving Corporate Accountability Through Mandatory Human Rights and Environmental Due Diligence - Daniel Maluțan; Teodora Maria Rusu; Daiana Eniu (Journal of Research and Innovation for Sustainable Society)
The last decades are indicative of an increasing global attention on the negative externalities that come from business operations: human rights violations and environmental harms related to business operations. Globalization has led to increasingly complex, dynamic and non-transparent global supply and value chains, thus making the burden of protecting human rights and environment even more difficult. The concept of mandatory human rights due diligence has been increasingly endorsed and proclaimed as a necessary solution to address these issues. This research aims to assess the ability of such a regulatory tool to serve as an instrument to protect human rights and the environment throughout the supply chain. The first part dives into examining recent developments in human rights due diligence adopted in the European Union. The second part of the research comprises an indepth assessment of the most recent legislative Draft proposed by the European Commission which aims to introduce an EUwide mandatory sustainability due diligence corporate duty. The last part is a doctrinal analysis of Corporate Governance which proves its important role in addressing human rights and environmental issues, as it is a tool for integrating the mandatory due diligence into the organisational culture of a business. The assessment of current national mandatory due diligence regulations shows that companies are not incentivized to develop a holistic approach but rather to focus on specific issues that are targeted through legislation. Moreover, they often apply only to certain categories of companies based on domicile or country of operation and number of employees or turnover which leads to fragmentation and discrepancies between states. The European Proposal is revolutionary in many aspects as it introduces a comprehensive human rights due diligence mechanism for companies. However, the provisions of the current draft have many weaknesses and loopholes that are likely to jeopardize the Directive’s effectiveness